Corruption As A Violation Of The Right To Education In Indonesia: A Constructivist Approach - Juwita, Ratna (Jurnal Hukum & Pembangunan, 2017)
This paper analyzes the relationship between corruption and realization of human rights in a specific case, the realization of the right to education by utilizing human rights standards concerning the right to education as the parameter of human rights realization. An Indonesian case law about corruption of Bantuan Operasional Sekolah funds in Malang is selected as primary legal data in this paper to provide empirical evidence one of the cases of corruption in education sector. Norm entrepreneurship as part of contructivist theory is selected to explain the phenomenon of emerging scholarly studies and discussion about corruption as a violation of human rights and this paper aims to draw the link between corruption and its negative impact to the realization of human rights in case analysis